Tofacitinib in the treatment of ulcerative colitis: efficacy and safety from clinical trials to real-world experience. (May 2019) - D'Amico, Ferdinando; Parigi, Tommaso Lorenzo; Fiorino, Gionata; Peyrin-Biroulet, Laurent; Danese, Silvio
Tofacitinib is an oral small molecule directed against the JAK/STAT pathway, blocking the inflammatory cascade. Oral formulation of tofacitinib has recently been approved for the treatment of patients with moderate–severe ulcerative colitis. Its efficacy and safety have been demonstrated in three phase III clinical trials and confirmed by promising real-life data. The purpose of this review is to summarize the available evidence on the efficacy and safety of tofacitinib and to define its role and position in the treatment algorithms for patients with ulcerative colitis.